Effect of Guided Imagery, Sports Activity & Composite Training in the Management of Nomophobia - Singh, Divyanshu Kumar; Sharma, Dr Neelam K (South Eastern European Journal of Public Health, 2024)
Nomophobia, the fear of being without a mobile phone, has become a prevalent issue in modern society. This study aimed to investigate the effectiveness of three intervention approaches in managing nomophobia: guided imagery, sports activity, and composite training. For data Self-made nomophobia questionnaires were applied on 200 college student samples aged 18-24, out of which 80 nomophobic students were selected. Participants were randomly assigned to one of the three intervention groups or a control group. The guided imagery group engaged in relaxation techniques and visualization exercises, while the sports activity group participated in physical activities. The composite training group received a combination of guided imagery and sports activities. The control group did not receive any intervention. Nomophobia levels were assessed using the Nomophobia Questionnaire (NMP-Q) before and after the interventions. Results showed that all three intervention groups experienced a significant reduction in nomophobia levels compared to the control group. The sports activity group demonstrated the most substantial decrease in nomophobia scores. The findings suggest that a combined approach of guided imagery and sports activity may be the most effective in managing nomophobia among college students aged 18-24. These insights contribute to developing targeted strategies to address the growing concern of nomophobia and its potential negative impacts on the mental health and well-being of young adults.